2016
DOI: 10.1177/194008291600900114
|View full text |Cite
|
Sign up to set email alerts
|

Road-Edge Effects on Herpetofauna in a Lowland Amazonian Rainforest

Abstract: The impact of roads on the flora and fauna of Neotropical rainforest is perhaps the single biggest driver of habitat modification and population declines in these ecosystems. We investigated the road-edge effect of a low-use dirt road on amphibian and reptile abundance, diversity, and composition within adjacent lowland Amazonian rainforest at San José de Payamino, Ecuador. The road has been closed to vehicle traffic since its construction in 2010. Thus, effects from vehicle mortality, vehicle-related pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
(72 reference statements)
1
10
0
1
Order By: Relevance
“…Lastly, diversity of leaf-litter and semi-aquatic amphibians is positively associated with environmental variables/habitat structures such as understorey density, tree density and temperature. The proportional relationship between diversity and tree density observed in this study was likewise observed in existing literature 40 . Higher tree density provides the necessary habitat conditions for typical rainforest composition of amphibian species 41 .…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, diversity of leaf-litter and semi-aquatic amphibians is positively associated with environmental variables/habitat structures such as understorey density, tree density and temperature. The proportional relationship between diversity and tree density observed in this study was likewise observed in existing literature 40 . Higher tree density provides the necessary habitat conditions for typical rainforest composition of amphibian species 41 .…”
Section: Discussionsupporting
confidence: 89%
“…Based on our literature review, we determined that specific taxa would be affected by road noise, light, temperature change or other effects at different widths and thus we chose 100 m (small carnivores and rodents, [39]; birds, [14], amphibians [14, 40]), 500 m (mid-sized carnivores, [41] and 1000 m (ungulates [39, 42]) from roads to account for impacts of forest loss and edge effects due to roads on various species. While we recognized that tropical ecosystems and species may vary in their response to traffic on roads, research on specific distances affecting tropical species is relatively rare.…”
Section: Methodsmentioning
confidence: 99%
“…Demand for expanding road networks has been concomitant with mass production of automobiles, and the pervasiveness of impacts of roads on biodiversity has long been recognized (Coffin, 2007;Stoner, 1925Stoner, , 1936. Roads fragment the landscape by creating edge effects and inhibiting dispersal or movement and expose animals to traffic collisions and mortality as well as alter assemblage composition (Coffin, 2007;Laurance, Goosem, & Laurance, 2009;Maynard, Aall, Saenz, Hamilton, & Kwiatkowski, 2016). This in turn can affect ecological and evolutionary dynamics by reducing effective population size, skewing sex ratios, and reducing genetic diversity (Balkenhol & Waits, 2009).…”
Section: Introductionmentioning
confidence: 99%